Saint Augustin, lecteur de Perse et de Juvenal - Sarr, Pierre (Gerión. Revista de Historia Antigua, 2006)
Abstract; Ecclesiastical man, sain Augustine is not less a familiar of traditional culture. Its works abounds in references to the classic authors, who they are playwrights, historians, philosophers or poets. The Correspondance and the City of God offer an example of it to us, through the quotations that the bishop of Hippone made of Perse and Juvenal. He is pressed on these two satiricals poets to refute criticisms that the pagans address to christians, to speak in praise of the virtue, to condemn the love of the purely human praises and to rise against all those who are forced themselves to know the end of time. Through the reading and the use which he makes of Perse and Juvenal, saint Augustine shows that he is not separated from the pagan world and that he adheres to the values recognized by everybody. However, the bishop does not hesitate to move away from these authors each time that he wants to propose the primacy of christianism on paganism.